2000
DOI: 10.1161/01.atv.20.6.1688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antioxidants and HDL on Glycated LDL–Induced Generation of Fibrinolytic Regulators From Vascular Endothelial Cells

Abstract: Abstract-Hyperglycemia and dyslipoproteinemia are biochemical markers of diabetes mellitus (DM). Elevated levels of plasminogen activator inhibitor-1 (PAI-1) with and without reduction of tissue plasminogen activator (tPA) in plasma have been frequently found in patients with DM. Our previous studies indicated that glycation enhances low density lipoprotein (LDL)-induced production of PAI-1 and further decreases tPA generation in vascular endothelial cells (ECs). The present study demonstrated that treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 38 publications
4
34
1
1
Order By: Relevance
“…Our previous studies indicated that the LDL-induced moderate increase in PAI-1 generation from EC may be attenuated by an antioxidant (21), which is an indication that cell-mediated oxidative modification contributes to PAI-1 upregulation in EC induced by LDL. The combination of the present and previous findings suggests that oxidative modification plays critical roles in LDL or its modified forms induced upregulation of HSF1 and PAI-1 in cultured vascular EC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous studies indicated that the LDL-induced moderate increase in PAI-1 generation from EC may be attenuated by an antioxidant (21), which is an indication that cell-mediated oxidative modification contributes to PAI-1 upregulation in EC induced by LDL. The combination of the present and previous findings suggests that oxidative modification plays critical roles in LDL or its modified forms induced upregulation of HSF1 and PAI-1 in cultured vascular EC.…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported that CLDL increased the release of PAI-1 from cultured HUVEC or HCAEC (21). The influence of other types of oxidized LDLs on PAI-1 expression, or that of CLDL on cell-associated PAI-1 abundance in EC, remains uncharacterized.…”
Section: Effects Of Oxidized Ldls On Nox2 Expression In Ecmentioning
confidence: 98%
“…LDL may be oxidatively modified by a prolonged incubation with endothelial cells (44). A previous study in our group demonstrated that antioxidants reduced the abundance of lipid peroxides in LDL and prevented LDL-induced release of PAI-1 from endothelial cells (15). The effects of LDL on HSF1 and PAI-1 after a prolonged incubation with endothelial cells may result, at least in part, from cell-mediated oxidative modification on LDL.…”
Section: Hsf1 In Glycated Ldl-induced Pai-1mentioning
confidence: 91%
“…Seed human umbilical vein endothelial cells (HUVECs) were obtained from American Type Culture Collection (Manassas, VA). Cells were grown in F12K medium (Gibco, Burlington, ON, Canada) containing 10% FCS, 0.1 mg/ml heparin, and 30 g/ml endothelial cell growth supplements (Sigma) (15). Seed human coronary arterial endothelial cells (HCAECs) and cultured supplements were obtained from Clonetics (San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation